Cumulative effects of multiple pains sites in youth with chronic pain - Basch, Molly C. (Eur J Pain, 2018)
BACKGROUND: The experience of persistent pain in multiple locations is common in youth. Based on current literature, youth with multiple pain sites (MPS) are at risk of experiencing poorer emotional outcomes and a spread of symptoms into late adolescence and adulthood. Little is known regarding the association between MPS with physical and school functioning domains, particularly after initiation of multidisciplinary pain treatment. Therefore, the objective of this study was to examine the association of MPS with disability and school functioning among youth with chronic pain. METHODS: A total of 195 patients with chronic pain, aged 8–17, and their parents completed measures assessing patient distress and functioning at a multidisciplinary pain clinic evaluation and at 4-month follow-up. RESULTS: At evaluation, 63% of patients presented with MPS; 25% reporting MPS endorsed pain in five or more locations. When controlling for relevant demographic and emotional distress factors, MPS was associated with lower school functioning at evaluation with a persistent trend at follow-up. Although MPS was not a significant predictor of pain-related disability at evaluation, it emerged as significant at follow-up. CONCLUSIONS: Potentially due to the MPS load and the inverse effects that such a pain state has on function, such patients may be at-risk for poorer health and school-related outcomes. The mechanisms influencing these relationships appear to extend beyond psychological/emotional factors and warrant further investigation in order to aid in our understanding of youth with MPS. SIGNIFICANCE: Youth with MPS may be at risk for experiencing poorer physical and school functioning in comparison to single-site peers, despite treatment initiation. Further research is warranted in order to inform assessment and treatment approaches for this subgroup of patients.